On two species of Aniptumnus Ng, 2002 (Crustacea: Brachyura: Pilumnidae) from India, with a description of a new species from the coast of Kerala - Hari, P. Praved; Hershey, N. Regina; Mendoza, Jose Christopher E. (Zootaxa, 2022)
The taxonomy of two species of Indian pilumnid crabs is treated herein. Heteropanope neolaevis Deb, 1985, originally described from northeastern India, is retained in the genus Aniptumnus Ng, 2002 as a valid species and removed from synonymy with Aniptumnus quadridentatus (De Man, 1895). A new species, Aniptumnus bijoyi, is described from southwestern India, based on distinguishing features in the carapace, thoracic sternum, pereopods and gonopods. With these developments, five species of Aniptumnus are now recognized.